PRINCIPLES OF SCORE DEFINITION OF TECTONIC FACIES ON THE PETROACOUSTIC DATA FOR EXAMPLE OF METAMORPHIC ROCKS OF KRYVYI RIG REGION (“SUPUTNYK”-2) - Bezrodniy, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Methodology of petroacoustic analysis of tectonic facies that enables the qualitative and quantitative assessment developed. Fact that the level of deformation changes may be measured by the values of the acoustic and elastic anisotropy is shown.